(untitled) (American Journal of Business Management, Economics and Banking, 2023)
Currently, innovation is becoming one of the most characteristic features of economic development. Not long ago, this name reminded of something exotic, unknown and not very clear even among professionals, but now the innovation itself and its concepts are rapidly conquering the world. The international capital market, which plays a significant role in the innovation process and turns innovation into a strategic resource for enterprises, is expanding, and new financial structures are helping it in this regard. The experience of developed countries shows that innovation is often hindered by people’s direct negative attitudes and attitudes. However, a paradoxical situation is developing in Uzbekistan, that is, the whole society expresses positive attitude and support to innovative processes.